Identification of Soil-Transmitted Helminths in Soil of Sheep Farm in Manggis Village, Serbajadi District, Serdang Bedagai Regency - Natasya Cornelia Tesalonika; Yoan Carolina Panggabean; Merina Panggabean; Nindia Sugih Arto (Sumatera Medical Journal, 2023)
Background: More than one and a half million of whole world population are infected by Soil Transmitted Helminths. The most common types of Soil Transmitted Helminths found in human are Ascaris lumbricoides, Trichuris trichiura and Hookworm (Necator americanus and Ancylostoma duodenale). Soil Transmitted Helminths infections are usually found on individuals with poor hygiene, low socioeconomic status, and high risk occupations, such as sheep farmer. Sheep farming in Indonesia is generally a small-scale farm with modest technology. Livestock herding on the pasture may cause the livestock to consume Soil Transmitted Helminths-contaminated grass. Soil is the medium for the maturing of Soil Transmitted Helminths fertilized egg into infective form. Modest handling aspect and poor sanitation allow Soil Transmitted Helminths to be found in farm soil. Objective: To identify Soil Transmitted Helminths in the soil of a sheep farm in Manggis Village, Serbajadi District, Serdang Bedagai Regency. Methods: This observational descriptive study was conducted with cross-sectional approach. 100 of soil samples were collected per 8 square meters through quota sampling from a sheep farm in Manggis Village, Serbajadi District, Serdang Bedagai Regency. The data was collected by carrying out flotation technique in laboratory. Results: Soil Transmitted Helminths eggs were discovered in 17 (17%) out of 100 samples, Hookworm eggs in 14 samples (14%), and Ascaris lumbricoides eggs in 5 (5%) samples. Conclusion: There are Soil Transmitted Helminths in soil of the sheep farm in in Manggis Village, Serbajadi District, Serdang Bedagai Regency.